Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Untuk Berkarir Di Bank Syariah (Studi Pada Mahasiswa Pasca Magang Program Studi Perbankan Syariah Di Kota Semarang) - Nurhayati Al Ismiarif; Siti Hasanah; Ida Nurhayati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study aims to analyze the significant effect of the work environment, job market considerations, internship experience, motivation, and financial rewards on student interest in pursuing a career in Islamic banking among post-internship students of the Islamic Banking study program in Semarang City, either simultaneously or partially.The population in this study were post-internship students of the Islamic banking study program in the city of Semarang. The sampling technique used was Accidental Sampling, which is a sampling technique based on chance, that is, anyone who coincidentally meets a researcher can be used as a sample.The data used in this study are primary data obtained through questionnaires. The data analysis model uses multiple linear regression analysis models. While the data analysis technique uses the F-statistical test, the coefficient of determination (R2), and the t-statistical test which is processed using the SPSS 25 program.The results of hypothesis testing and discussion show that the work environment, job market considerations, internship experience, motivation, and financial rewards simultaneously have a significant effect on student interest in pursuing a career in Islamic Banks in post-internship students of the Islamic Banking study program in Semarang City. Partially, work environment and motivation have a positive and significant effect. Meanwhile, consideration of the job market, internship experience, and financial rewards have a positive and insignificant effect on students' interest in a career in Islamic Banks for post-internship students of the Islamic Banking study program in Semarang City.